1999
DOI: 10.2134/agronj1999.914631x
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Nitrogen Content of Corn under Different Tillage Practices

Abstract: Furthermore, tillage practices cause soil disturbance, which may contribute to a decline in available soil N The objective of the study was to determine whether tillage and (Stevenson, 1965; McCarthy et al., 1995) due to mineralresidue practices have a significant effect on the yield and N content of corn (Zea mays L.) under nonlimiting soil N conditions. Nitrate ization of organic matter, which is vulnerable to oxileaching has been identified as a source of non-point-source pollution. dation.By identifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 20 publications
(26 reference statements)
1
33
1
Order By: Relevance
“…No compaction or surface crusting would be expected for these soils under these conditions. This lack of consistent response to tillage has also been reported by Licht and Al-Kaisi (10) and by Mehdi et al (12).…”
Section: Discussionsupporting
confidence: 82%
“…No compaction or surface crusting would be expected for these soils under these conditions. This lack of consistent response to tillage has also been reported by Licht and Al-Kaisi (10) and by Mehdi et al (12).…”
Section: Discussionsupporting
confidence: 82%
“…Thick crop residue cover can reduce crop emergence particularly in temperate climates with cool and wet soils during the spring (Mehdi et al, 1999). Thus, a judicious removal of residue mulch can promote early emergence.…”
Section: A Crop Growth and Heightmentioning
confidence: 99%
“…The enhanced water movement through soil macro pores in the profile increases the potential of soluble nitrates movement under no tillage scenario (Ahmad et al, 2009). Ground water pollution, due to nitrate (NO 3 -) leaching, causes serious problems concerning human health and the environment in many developing as well as developed countries (Benbi et al, 1991, Carman 1997, Wilson et al, 1999 Mehdi et al, (1999) and Sainju and Singh (2001) concluded that the application of tillage practice in crop production system is important for the plant growth as it affects soil environmental components. It can also have its influence on the N availability and N pool status for maintaining proper nutrient levels in the soil environment system.…”
Section: Introductionmentioning
confidence: 99%